(untitled) (Ottawa, Canada, 1998)
For the large number of developing countries undergoing significant structural transformations, one of the most important and controversial adjustment areas is that of financial markets. Focusing on the role of the institutional and enabling environment within which financial reform occurs, and the integration of principles of finance with more macro-economic approaches to the subject, this book contains case studies of reform experiences in Argentina, India, Nigeria, Turkey and Uruguay. Thematic papers cover topics such as the "go slow" versus "big bang" approach, and the particular problem of bank-firm inter-linkages in Eastern Europe.
Keywords: Finance,Structural adjustment (Economic policy),Monetary policy; Developing countries,Developing countries,Developing countries